The Role of Management Practice and Business Environment in Promoting Firm Innovativeness - Strugar Jelaca, Maja (Industrija, 2016)
The aim of this research is to identify the relationships between management practices and firm innovativeness on the one hand and business environment and firm innovativeness on the other. The research subject is the new management practices explored through two sides of the coin of management, like innovative management functions and roles, factors of dynamic business environment and organization innovation rate. The methodology that was used includes the application of statistical methods such as Spearman’s correlation and MANOVA. Relying on data from 50 large organizations in Serbia, this study shows that, as well as some managerial roles, innovation-oriented planning, staffing leading and controlling stand in positive correlation to higher firm innovativeness. Furthermore, it explains differences in the degree of firm innovativeness depending on the nature of planning, staffing and leading. Given that firms usually operate in a dynamic business environment, empirical results regard changes in customer preferences, competition and technology as important contingency factors of firm innovativeness. The obtained results are useful for encouraging innovative ways of doing business which can be the base for developing a practical framework of new management practices which enhance firm innovativeness. However, empirical studies investigating the relative importance of innovative management practices are scarce, and therefore our study will attempt to fill the gap and open the way for further research into this area.